2013
DOI: 10.1021/ja410866w
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Self-Assembly of Supported Membranes Using Sacrificial, Anhydrobiotic Sugar Coats

Abstract: Borrowing principles of anhydrobiosis, we have developed a technique for self-assembling proteolipid-supported membranes on demand--simply by adding water. Intact lipid- and proteolipid vesicles dispersed in aqueous solutions of anhydrobiotic trehalose are vitrified on arbitrary substrates, producing glassy coats encapsulating biomolecules. Previous efforts establish that these carbohydrate coats arrest molecular mobilities and preserve native conformations and aggregative states of the embedded biomolecules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…During the vitrification of trehalose and removal of water from the environment, embedded SUVs undergo significant shape deformation, which is restored once water is added back to the system. 16 This shape deformation likely plays an important role in determining minimum distances for eliminating cross talk of adjacent spots, as this may cause the bulk deposited vesicle surface area to laterally stretch from the arrayed spot. Nevertheless, this does not seem to have any negative impact on results, even with spacing <100 μm.…”
Section: Spr Imaging Of Multielement Slb Arraysmentioning
confidence: 99%
See 2 more Smart Citations
“…During the vitrification of trehalose and removal of water from the environment, embedded SUVs undergo significant shape deformation, which is restored once water is added back to the system. 16 This shape deformation likely plays an important role in determining minimum distances for eliminating cross talk of adjacent spots, as this may cause the bulk deposited vesicle surface area to laterally stretch from the arrayed spot. Nevertheless, this does not seem to have any negative impact on results, even with spacing <100 μm.…”
Section: Spr Imaging Of Multielement Slb Arraysmentioning
confidence: 99%
“…Nevertheless, this does not seem to have any negative impact on results, even with spacing <100 μm. 16 This was further explored by spotting a microarray substrate for biological recognition, that on hydration resulted in 800 × 800 μm POPC membranes containing either GM1, GM2, GM3, or no receptors, as a negative control. Previous work has shown that cholera toxin has a very low affinity toward GM2 and GM3 compared to GM1 and no affinity toward POPC alone.…”
Section: Spr Imaging Of Multielement Slb Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…5). More recent efforts have been made to preserve membrane structure during storage and transport, which may have important implications toward advancing commercialization and widespread adaptation of these biomimetic interfaces [77, 78]. …”
Section: Lipid Membranes and Nanopore Signal Transductionmentioning
confidence: 99%
“…Recently, trehalose has been used to prepare storable and triggered substrate-mediated vesicle fusion. 151 Addition of a synthetic trehalose glycolipid provided air stability at doping densities as low as 20% in the case of supported lipid monolayers.…”
Section: Air Instability Of Slbsmentioning
confidence: 99%